Analysis of Co-Production in the Implementation of the Healthy Kitchen Service to Combat Stunting (DASHAT): Community Empowerment Through Social Entrepreneurship for Family Nutritional Security at the Ministry of Population and Family Development/National Population and Family Planning Board - Ika Restu Putri Saraswati; Bintoro Wardiyanto (Publikasi Indonesia, 2026)
Stunting remains a major public health challenge in Indonesia, with a national prevalence of 19.8% as of 2024. The Dapur Sehat Atasi Stunting (DASHAT), or Healthy Kitchen to Combat Stunting program, launched by the Ministry of Population and Family Development (Kementerian Kependudukan dan Pembangunan Keluarga/BKKBN), is a co-production-based public service innovation that integrates community empowerment with a sociopreneurship approach. This study aims to analyze the implementation of co-production within the DASHAT program and its implications for community empowerment in achieving household nutritional security. This study employs a descriptive qualitative approach within the New Public Governance (NPG) framework, examining four dimensions of co-production co-commissioning, co-design, co-delivery, and co-assessment through document analysis and descriptive-analytical techniques. The findings reveal that DASHAT has succeeded in shifting the paradigm from passive service recipients to active co-producers through mechanisms of local food processing training, the establishment of family business groups (kelompok usaha keluarga), and participatory evaluation. The sociopreneurship approach reinforces the sustainability of the program by simultaneously generating economic and social value. Key challenges include the limited facilitative capacity of implementing officials, disparities in participation levels across community groups, and the sustainability of program funding. This study recommends strengthening facilitative leadership capacity, developing digital platforms for participatory monitoring and evaluation, and institutionalizing co-production mechanisms within an appropriate regulatory framework to accelerate stunting reduction. This research contributes to the co-production literature by demonstrating its application in the context of community-based nutrition interventions in developing countries.